Changes in calsequestrin, TNF-alpha, TGF-beta and MyoD levels during the progression of skeletal muscle dystrophy in mdx mice: a comparative analysis of the quadriceps, diaphragm and intrinsic laryngeal muscles - Maranhao, Juliana Barros; Moreira, Drielen de Oliveira; Mauricio, Adriana Fogagnolo; Carvalho, Samara Camacari de; Ferretti, Renato [UNESP]; Pereira, Juliano Alves; Santo Neto, Humberto; Marques, Maria Julia (Wiley-Blackwell, 2015)
In Duchenne muscular dystrophy (DMD), the search for new biomarkers to follow the evolution of the disease is of fundamental importance in the light of the evolving gene and pharmacological therapies. In addition to the lack of dystrophin, secondary events including changes in calcium levels, inflammation and fibrosis greatly contribute to DMD progression and the molecules involved in these events may represent potential biomarkers. In this study, we performed a comparative evaluation of the progression of dystrophy within muscles that are differently affected by dystrophy (diaphragm; DIA and quadriceps; QDR) or spared (intrinsic laryngeal muscles) using the mdx mice model of DMD. We assessed muscle levels of calsequestrin (calcium-related protein), tumour necrosis factor (TNF-alpha; pro-inflammatory cytokine), tumour growth factor (TGF-beta; pro-fibrotic factor) and MyoD (muscle proliferation) vs. histopathology at early (1 and 4 months of age) and late (9 months of age) stages of dystrophy. Fibrosis was the primary feature in the DIA of mdx mice (9 months: 32% fibrosis), which was greater than in the QDR (9 months: 0.6% fibrosis). Muscle regeneration was the primary feature in the QDR (9 months: 90% of centrally nucleated fibres areas vs. 33% in the DIA). The QDR expressed higher levels of calsequestrin than the DIA. Laryngeal muscles showed normal levels of TNF-alpha, TGF-beta and MyoD. A positive correlation between histopathology and cytokine levels was observed only in the diaphragm, suggesting that TNF-alpha and TGF-beta serve as markers of dystrophy primarily for the diaphragm.
Keywords: calsequestrin; dystrophy; mdx; tumour growth factor-beta; tumour necrosis factor-alpha